CONSUMER PROTECTION AS CONCURRENT CREDITORS FOR DISTRIBUTION OF BOEDEL BANKRUPTCY DEVELOPER PROPERTY TYPE OF HOUSING - Ayub Fatahillah; Sri Astutik (Awang Long Law Review, 2021)
As a result of a property developer going bankrupt, housing consumers suffer losses, because Article 37 of the Bankruptcy Law & PKPU has not provided the same protection as the Consumer Protection Act. This study aims to determine the position of consumers as concurrent creditors and their legal remedies. This normative legal research is analyzed using the deductive method, which is a way of analyzing that is based on general laws and regulations to find answers to the legal issues studied. The results of the study, that consumers are placed as Concurrent Creditors whose debt fulfillment is paid last. Efforts that can be made so that consumers can become creditors are prioritized by reviewing the rights and obligations in the Sale and Purchase Binding Agreement made based on the Regulation of the Minister of Public Works and Public Housing Number 11/PRT/M/2019 concerning the Preliminary Agreement System for the Sale and Purchase of Houses and based on the Decision Constitutional Court Number 67/PU-XI/2013 on review of Article 95 paragraph (4) of Law Number 13 of 2003 concerning Manpower, which states that, because workers do not participate in business, their payments can be prioritized over other Creditors. The decision can be applied to housing consumers who have already paid the money to the developer.